Palynology of the eocene esmeraldas formation, middle Magdalena Valley Basin, Colombia (2012)
The palynology of the Eocene Esmeraldas Formation in the Middle Magdalena Valley Basin, Colombia was analyzed in order to constrain the age of the unit. This formation is a very important oil reservoir in the Middle Magdalena Valley Basin, which is a product of the fragmentation of a Cenozoic foreland basin by the uplift of the Northern Andes. The lateral continuity of the formation, as well as its correlations with lithostratigraphic units in adjacent basins is not clearly understood. The Los Corros Fossil Horizon, a molluscan horizon in the upper part of the Esmeraldas Formation, has been used to trace the top of the formation. This horizon is not laterally continuous over the basin and its age is still debatable. Data from 82 samples from an outcrop section in the Nuevo Mundo Syncline area and from seven previously studied wells have been integrated with a palynological zonation of northern South America in order to date the Esmeraldas Formation. The age ranges from the late Early Eocene to the Late Eocene. The Esmeraldas Formation is correlative with the upper Picacho Formation and the lower part of the Concentracion Formation in the Eastern Cordillera, and the upper Mirador Formation and the base of the Carbonera Formation in the Llanos Foothills. The Los Corros Fossil Horizon is Late Eocene and is time-correlative with a marine transgression in the central Llanos Foothills. A non-metric multidimensional scaling analysis suggests that floras from the Middle Magdalena Valley were different from those in the Llanos Foothills area during the Middle to Late Eocene. This is apparently due to taphonomic effects. The results of this study will contribute to a better understanding of the overall evolution of the Middle Magdalena Valley Basin.